Pengaruh Pengetahuan Bisnis dan Lingkungan Keluarga Terhadap Minat Berwirausaha Pada Mahasiswa Prodi Perbankan Syariah IAIN Syaikh Abdurrahman Siddik Bangka Belitung - savitri, Destri; Irvani, Ahmad; Destiana, Yolanda (JYRS: Journal of Youth Research and Studies, 2024)
This research explains the problem of how business knowledge and family environment influence students' interest in entrepreneurship. Entrepreneurship is an important factor in the economic growth of a country. Entrepreneurs play a role in creating jobs, increasing competitiveness and encouraging innovation. This research method uses a type of quantitative research that uses primary data with a sample of 77 respondents. The data collection technique used was a questionnaire. The data analysis technique used is the classical assumption test, multiple linear regression analysis test, hypothesis testing and the research instrument uses SPSS version 22. The population in this research includes students from the 2020-2022 Sharia Banking study program at the Faculty of Sharia and Islamic Economics, IAIN Syaik Abdurrahman Siddik Bangka Belitung, totaling 326 students. Meanwhile, this research sample had 77 respondents. The results of this research show that there is a significant influence based on the results of the t test with significant business knowledge, the t value is 18,876, while the t table with degrees of freedom of 80 at alpha 0.05 is 1,664, so that H1 is accepted, H0 is rejected or if you look at the significance it is 0.000 < 0.05. Meanwhile, the Fcount value was 280.542. Thus Fcount (280.542) > Ftable 3.12, so H0 is rejected and Ha is accepted or if you see a significant value of 0.000 < 0.05. So it can be concluded that the variables Business Knowledge and Family Environment simultaneously have a positive and significant effect on the interest in entrepreneurship of Islamic banking study program students at IAIN Syaikh Abdurrahman Siddik Bangka Belitung.